Astrin: A Key Player in Mitosis and Cancer - Ying, Zhenguang (Front Cell Dev Biol, 2020)
Astrin, which is a spindle-associated protein, was found to be closely related to mitotic spindle formation and maintenance. It interacts with other spindle-related proteins to play a key role in maintaining the attachment of the kinetochore-microtubule and integrity of centrosomes and promoting the centriole duplication. In addition, Astrin was quite recently found to be abnormally highly expressed in a variety of cancers. Astrin promotes the development of cancer by participating in various molecular pathways and is considered as a potential prognostic and survival predictor.